L’enceinte gallo-romaine d’Angers devenue clôture canoniale : transformations, adaptations et déclassement d’une fortification (XIIIe-XVIe siècles) - François Comte (In Situ)
At Angers, the fortified wall dating from classical times lost its military and defensive vocations when it was included in the city of Saint Louis. Nonetheless, the wall was maintained, restored and its gates guarded up to the end of the Hundred Years’ War. The canons of the cathedral, who made their claustrum of this the wall, lost their fight to keep it in its integrity. Finally, the wall came to be hidden by new buildings and partial destruction of the wall continued up to the beginning of the nineteenth century.